Comparatively Low Temperature Synthesis, Characterization and Some Physical Studies on Transition Metal Vanadates (Journal of Scientific Research, 2021)
Pure transition metal vanadates NiV2O6 and CuV2O6 were successfully prepared via co-precipitation technique as low as at 600 °C. The crystal structure and their phase formation were confirmed by X-ray powdered diffraction. Both the compounds were identified to have a single-phase triclinic structure. The bonding characteristics were studied by FTIR spectroscopy. The temperature dependence of electrical resistivity of these vanadates shows a typical semiconducting nature of NiV2O6 and CuV2O6, consistent with their electronic band structures. The calculated band gap energy values of NiV2O6 and CuV2O6 were found to be 2.42 and 2.0 eV respectively, employing a DRS UV-Visible spectrophotometer. Magnetic susceptibility measurements and calculated Magnetic moments confirm their paramagnetic nature. The photocatalytic efficiency was investigated by photo-degradation of methylene blue (MB) solutions employing solar light and found to be promising photocatalysts.